Impact of fixed orthodontic appliances on quality of life among adolescents’ in India - Nagarajappa, Ramesh (J Clin Exp Dent, 2014)
Context: Malocclusion can seriously impair quality of life and they may affect various aspects of life, including function, appearance, interpersonal relationships and even career opportunities. Objectives: To assess and determine various factors that may influence the impact of orthodontic treatment on the quality of life of adolescents. Study Design: Cross sectional study in adolescents of Moradabad was conducted on 109 males and 113 females (n=222) adolescents having a fixed orthodontic appliance, aged 13 to 22 years (mean 17.5±1.5). A pre-structured questionnaire designed by Mandall et al, with nine conceptual impact sub-scales to highlight the problem faced by the patient in daily life after wearing the appliance was used to collect the data. Unpaired t-test was used to determine the statistical significance and the influence of variables were analysed using multiple linear regression analysis. Results: Factors which demonstrated high impact were oral hygiene (Mean=3.42; SD=0.78) followed by time constraints (Mean=3.23; SD=0.72) and physical impact (Mean=3.00; SD=0.61). Gender difference showed statistical significance in social impact (p=0.009), time constraints (p=0.001) and travel or cost implications (p=0.009). Internal reliability of the questionnaire ranged from low to good (Cronbach’s alpha 0.29-0.81). Test-retest reliability ranged from an intra-class correlation coefficient 0.09-0.42. Conclusions: Patients who had been comprehensively informed about their treatment had greatest levels of satisfaction and compliance with treatment. Younger patients showed an earlier adaptation to treatment with fixed appliances which influenced the treatment to be started at the earliest possible age. Key words:Impact, malocclusion, quality of life.